Economic Benefits of Foreign Sourced Germplasm in Domestic Crop Improvement Program: A Case of an Improved Khumal-4 Rice Variety in Nepal - Gauchan, D; Pant, K P; Joshi, B K (Agronomy Journal of Nepal, 2016)
This study assesses economic benefits of international exchange and flow of key rice germplasm in Nepal under globally operated multilateral system of facilitated access using a case of an improved rice variety Khumal-4. Khumal-4 rice is popular and widely grown in mid hills region of Nepal which was developed by crossing a high yielding dwarf foreign sourced germplasm IR-28 with a local Nepali variety Pokharilo Masino. Economic benefits of Khumal-4 rice adoption and impact was analysed using economic surplus model, where additional productivity and profitability gained from developing Khumal-4 was estimated in monetary value in comparison with existing farmers’ variety Pokharilo masino. The finding showed that Khumal-4 covered 9% of rice area in the mid-hills and 7% in the mountains during year 2010-12 years covering about 40 thousand hectares of rice area. Data show that there is a clear yield gain of 1.25 mt per hectare with cost in rice yield equivalent when farmers switch from traditional Pokhareli Masino to improved Khumal-4 variety. Estimation of additional revenue per hectare with total adoption area of Khumal-4 in prevailing market price in Nepal was NRs 1.07 billion (US 11 million) per annum. This is reasonable economic benefits obtained annually from flow of foreign sourced genes (IR-28) for the development of an improved Khumal-4 rice variety in Nepal. This finding indicates that access to foreign germplasm is important for ensuring national food security and gaining higher economic benefits in the country. Agronomy Journal of Nepal (Agron JN) vol. 4, 2016